PROHIBITED SUBSIDIES UNDER THE WTO AGREEMENT ON SUBSIDIES AND COUNTERVAILING MEASURES (SCM AGREEMENT): A COMPREHENSIVE LEGAL ANALYSIS - Azizbek Toyirov (Innovate Conferences, 2025)
The multilateral trading system under the auspices of the World Trade Organization (WTO) is designed to ensure fair and open trade among member states. One of the central instruments in this framework is the Agreement on Subsidies and Countervailing Measures (SCM Agreement), which regulates the use of subsidies and the measures that may be taken to counteract their effects. The SCM Agreement divides subsidies into three principal categories: prohibited, actionable, and non-actionable. Among these, prohibited subsidies are considered the most harmful due to their inherently trade-distortive nature. This article provides a comprehensive legal analysis of prohibited subsidies under the SCM Agreement, with particular emphasis on the provisions of Article 3 and relevant jurisprudence.